Evaluation of Role of Ultra Sound Guided Fine Needle Aspiration Cytology for Diagnosis of Ovarian Lesions with Particular References to Diagnostic Pitfalls (Bangladesh Journal of Medical Science, 2014)
Background: Ovarian lesions are quite common among females of all age groups. Ovarian cancers account for 6% of female malignancy. Ultrasonography (USG) can help in proper identification and categorization of these lesions. Fine Needle Aspiration Cytology (FNAC) under USG guidance can be an effective modality for early diagnosis of ovarian masses. Aims And Objectives: To evaluate the role of USG guided FNAC over ovarian space occupying lesions (SOLs) for proper categorization into non-neoplastic, benign & malignant variants and to identify possible underlying causes of cytological misdiagnosis, if any, in comparison to histopathological diagnosis. Materials and Methods: FNAC under USG guidance were performed over one hundred and sixteen cases with radiologically proved ovarian SOLs during a period of five years. Aspirated materials were interpreted as non- neoplastic, benign or malignant lesions. Histopathological study was possible in 47 of these cases. Results: Out of 116 aspirations, non-neoplastic, benign and malignant diagnosis were given in 51, 42 & 23 cases, respectively. During histopathological correlation 41 out of 47 cases (87.2%) show exact cytohistological parity. Rest six cases with cytological misdiagnosis were discussed in detail. Conclusion: USG guided FNAC can effectively diagnose ovarian lesions in more than 87% cases. Scrutiny about failed diagnosis will help to improve accuracy in future. DOI: http://dx.doi.org/10.3329/bjms.v13i2.14520 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.158-162